Hypertrophic cardiomyopathy-linked mutation in troponin T causes myofibrillar disarray and pro-arrhythmic action potential changes in human iPSC cardiomyocytes. (January 2018) - Wang, Lili; Kim, Kyungsoo; Parikh, Shan; Cadar, Adrian Gabriel; Bersell, Kevin R.; He, Huan; Pinto, Jose R.; Kryshtal, Dmytro O.; Knollmann, Bjorn C.
Abstract: Background: Mutations in cardiac troponin T (TnT) are linked to increased risk of ventricular arrhythmia and sudden death despite causing little to no cardiac hypertrophy. Studies in mice suggest that the hypertrophic cardiomyopathy (HCM)-associated TnT-I79N mutation increases myofilament Ca sensitivity and is arrhythmogenic, but whether findings from mice translate to human cardiomyocyte electrophysiology is not known. Objectives: To study the effects of the TnT-I79N mutation in human cardiomyocytes. Methods: Using CRISPR/Cas9, the TnT-I79N mutation was introduced into human induced pluripotent stem cells (hiPSCs). We then used the matrigel mattress method to generate single rod-shaped cardiomyocytes (CMs) and studied contractility, Ca handling and electrophysiology. Results: Compared to isogenic control hiPSC-CMs, TnT-I79N hiPSC-CMs exhibited sarcomere disorganization, increased systolic function and impaired relaxation. The Ca-dependence of contractility was leftward shifted in mutation containing cardiomyocytes, demonstrating increased myofilament Ca sensitivity. In voltage-clamped hiPSC-CMs, TnT-I79N reduced intracellular Ca transients by enhancing cytosolic Ca buffering. These changes in Ca handling resulted in beat-to-beat instability and triangulation of the cardiac action potential, which are predictors of arrhythmia risk. The myofilament Ca sensitizer EMD57033 produced similar action potential triangulation in control hiPSC-CMs. Conclusions: The TnT-I79N hiPSC-CM model not only reproduces key cellular features of TnT-linked HCM such as myofilament disarray, hypercontractility and diastolic dysfunction, but also suggests that this TnT mutation causes pro-arrhythmic changes of the human ventricular action potential. Graphical abstract: Summary of the generation and characterization of the hiPSC model, which describes how the HCM-linked TnT-I79N mutation can increase arrhythmia risk in humans. Highlights: TnT-I79N hiPSC-CMs reproduce key cellular features of clinical HCM. TnT-I79N mutation reduces Ca transients by increasing cytosolic Ca buffering. TnT-I79N mutation causes pro-arrhythmic action potential changes.